2015
DOI: 10.4102/sajems.v18i4.737
|View full text |Cite
|
Sign up to set email alerts
|

Foreign aid on economic growth in Africa: A comparison of low and middle-income countries

Abstract: Previous empirical studies on the effects of foreign aid on economic growth have generated mixed results that make it difficult to draw policy recommendations. The main reason for such mixed results is the choice of a single aggregate list of countries, regardless of the disparities in levels of development. This study therefore fills the development gap by disaggregating the African data into a panel of 20 middle-income and 19 low-income African countries over a period of 15 years between 1995 and 2010, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
2
20
0
1
Order By: Relevance
“…It shows that an increase of 1% in the AID, FDI, and DI leads to an increase in economic growth by 0.092, 0.146, and 0.118%, respectively. However, the positive relationship that is founded between AID and economic growth is in line with the prior studies of Alemu and Lee (2015), Dalgaard et al (2004), Jena and Sethi (2019), Karras (2006), Ndambendia and Njoupouognigni (2010), Sethi et al (2019), Sothan (2018), and Tait et al (2015), but contrary to Mallik (2008), Liew et al (2012), Niyonkuru (2016), and Yiew and Lau (2018), who found a negative impact of AID on growth in recipient countries. Besides, the positive nexus between FDI and economic growth is similar to previous empirical studies of Borensztein et al (1998), Emmanuel (2014), Olawumi and Olufemi (2016), Umoh et al (2012), Onuoha et al (2018), and Zekarias (2016), suggesting that FDI is an important vehicle for the transfer of technology, which contributes to technological progress and creates a spillover effect, and thereby raises the long‐term growth rate.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It shows that an increase of 1% in the AID, FDI, and DI leads to an increase in economic growth by 0.092, 0.146, and 0.118%, respectively. However, the positive relationship that is founded between AID and economic growth is in line with the prior studies of Alemu and Lee (2015), Dalgaard et al (2004), Jena and Sethi (2019), Karras (2006), Ndambendia and Njoupouognigni (2010), Sethi et al (2019), Sothan (2018), and Tait et al (2015), but contrary to Mallik (2008), Liew et al (2012), Niyonkuru (2016), and Yiew and Lau (2018), who found a negative impact of AID on growth in recipient countries. Besides, the positive nexus between FDI and economic growth is similar to previous empirical studies of Borensztein et al (1998), Emmanuel (2014), Olawumi and Olufemi (2016), Umoh et al (2012), Onuoha et al (2018), and Zekarias (2016), suggesting that FDI is an important vehicle for the transfer of technology, which contributes to technological progress and creates a spillover effect, and thereby raises the long‐term growth rate.…”
Section: Resultssupporting
confidence: 90%
“…Their empirical results showed that AID was positively associated with growth, whereas the volatility of AID hurts it. Alemu and Lee (2015) investigated the dynamic relationship between AID and economic growth for 39 African countries over the period 1995-2010 and found that AID promotes economic growth only in the low-income countries. Tait et al (2015) found that AID has a significant positive long-run effect on economic growth for 25 SSA countries over the period 1970-2012.…”
Section: Aid-economic Growth Nexusmentioning
confidence: 99%
“…In the context of some developing countries, political reforms, influx of foreign aid and foreign direct investments are bringing unprecedented opportunities for growth, employment, education and improvement in public health indices 34–38. At the same time, significant challenges remain in an effort to sustain the growth trajectories, reduce the prevalence of extreme poverty, and cut child stunting and mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Dreher et al (2015) pointed out that many of the developing countries receiving aids, poverty still looms large, and underdevelopment persists while concluding that there is no robust evidence that aid affects growth. On the other hand, Alemu and Lee (2015) in their work on the comparative analysis of the impact of foreign aid on Middle and Low-Income African countries concluded that aid has a significant positive impact on low-income countries arguing that criticisms of foreign aid is flawed. Galiani et al (2014) also pointed out that foreign aid has a sizable positive effect on economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%